Syntheses, Structures, Reactivities, and Dynamic Properties of Gyroscope-like Complexes Consisting of Rh(CO)(X) or Rh(CO)2(I) Rotators and Cage-like Trans Aliphatic Dibridgehead Diphosphine Stators - Estrada, Alexander L.; Wang, Leyong; Bhuvanesh, Nattamai; Hampel, Frank; Gladysz, John A. (Organometallics, 2022)
Square planar trans-Rh(CO)(Cl)[P((CH2)14)3P] (4c) is prepared from trans-Rh(CO)(Cl)[P((CH2)6CHâ CH2)3]2by a Câ C metathesis/hydrogenation sequence (41%). Additions of NaBr, NaI, or KSCN give the substitution products trans-Rh(CO)(X)[P((CH2)14)3P] (X = Br/I/-NCS, 5c/6c/7c, 97-44%). Additions of ZnPh2, MeLi, or NaBH4give trans-Rh(CO)(R)[P((CH2)14)3P] (R = Ph/Me, 8c/9c, â 94-89%) or trans-Rh(CO)(H2BH2)[P((CH2)14)3P] (10c, 99%). Reactions with BrCCl3or CO give the octahedral or trigonal bipyramidal addition products trans-Rh(CO)(Cl)(Br)(CCl3)[P((CH2)14)3P] (11c, 97%) or trans-Rh(CO)2(I)[P((CH2)14)3P] (12c, â 98%). The crystal structures of 5c, 6c, 8c, and 10c are determined. These and other data are used to calculate the dimensions of the rotators and void spaces of the diphosphine cages, aiding the interpretation of dynamic properties. Specifically, 4c-6c and 9c-10c exhibit a single set of seven CH213C NMR signals at room temperature, although three sets of seven are expected from symmetry (â facile 360° Rh(CO)(X) rotation); 7c-8c exhibit two sets of seven signals with a ca. 2:1 area ratio (â 90° Rh(CO)(X) rotation); 11c exhibits three sets of seven signals (no Rh(CO)(Cl)(Br)(CCl3) rotation). The barrier to Rh(CO)2(I) rotation in 12c is bounded as higher than that of Rh(CO)(I) rotation in 6c, but the rotamers preferentially interconvert via CO dissociation/addition. Reaction of 4c and excess PMe3gives trans-Rh(CO)(Cl)(PMe3)2(72%) and the dibridgehead diphosphine P((CH2)14)3P (58%). The latter reacts with [(OC)2Rh(μ-Cl)]2to regenerate 4c (58%).
CRIS-Team Scopus Importer:2022-04-22